2017
DOI: 10.1002/jssc.201601358
|View full text |Cite
|
Sign up to set email alerts
|

Method for improving accuracy in full evaporation headspace analysis

Abstract: We report a new headspace analytical method in which multiple headspace extraction is incorporated with the full evaporation technique. The pressure uncertainty caused by the solid content change in the samples has a great impact to the measurement accuracy in the conventional full evaporation headspace analysis. The results (using ethanol solution as the model sample) showed that the present technique is effective to minimize such a problem. The proposed full evaporation multiple headspace extraction analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…In MHE-GC measurements, a large sample weight is helpful for improving the sensitivity of the method [ 30 ]. However, using a larger sample size (weight) can cause lower detection efficiency because of the slower release of water from the core material in the flavor microcapsule sample [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In MHE-GC measurements, a large sample weight is helpful for improving the sensitivity of the method [ 30 ]. However, using a larger sample size (weight) can cause lower detection efficiency because of the slower release of water from the core material in the flavor microcapsule sample [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…A linear variation in the GC signal with respect to the sample size was observed from approximately 0 to 0.51 g. When the sample amount was more than 0.51 g, the A 1 value was lower than the actual value, resulting in an error in the test results. This outcome is because the total gas pressure in the headspace bottle is very high, resulting in pressure effects [ 30 , 31 ]. Therefore, 0.51 g was determined to be the maximum sample content for successfully measuring the moisture content in the samples.…”
Section: Resultsmentioning
confidence: 99%
“…The disadvantages regarding FESHS refer to the excessive inner pressure inside the sample vial as a source of operational problems [ 14 ]. In an attempt to alleviate this issue, strategies combining FET with SPME [ 14 ] or using a multiple headspace analysis [ 15 ] were reported. The main disadvantages of FEDHS, in turn, include the low sampling rate and the complex and expensive apparatus involved [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Headspace (HS) GC is an effective technique for the analysis of volatile compounds in the samples with a complicated matrix, with or without less sample pretreatment . In our previous studies, we have demonstrated the volatile tracer‐assisted HS‐GC techniques for indirectly determining the physical and chemical properties, e.g., the solubility of inorganic salt and the viscosity of concentrated pulping spent liquors .…”
Section: Introductionmentioning
confidence: 99%